Coupling Action of Cooling and Dynamic Load Impact on Deformation Characteristics of High-Salinity Saline Soils. (11th September 2021) - Zhang, Yu; Zou, Meisi; Tian, Runze; Xu, Anhua; Hou, Yunlong; Han, Bingbing; Li, Xuemei
Abstract : In order to grasp the characteristics and mechanism of saline soil deformation under the coupling action of cooling and dynamic load, three types of subgrade fillings from the Qarhan-Golmud Highway in Qinghai-Tibet Plateau were selected as experimental soil samples for the experimental study. Firstly, the freezing temperature experiment was carried out on SS (sandy silt) and HS (high-sulfate silty clay). The test results showed that the freezing temperature of SS is -0.32°C, while that of HC (high-chloride silty clay) and HS will not freeze at -20°C, due to the presence of salt. Secondly, the three soil samples were subjected to deformation characteristic test under coupling action of cooling and dynamic load, respectively, and the time history curve of temperature gradient change, the time history curve of the change rate of deformation, and deformation rate were summarized. Finally, the model of deformation rate vs. time and the model of change rate of deformation vs. deformation rate under the coupling action of cooling and dynamic load are proposed. The test results found that (1) the cooling rate of the temperature gradient curve of the three soil samples showed a rapid cooling rate in the early stage, and it tends to stabilize in the later stage. The distance of the 0°C line from the top gradually decreases, which is affected by the freezing temperature and the salt content. (2) Affected by the freezing temperature and salt type, SS exhibits frost heave, and HS and HC appear to settlement. The final deformation is 1.0%, -0.73%, and -1.10%, respectively. (3) The model of deformation rate vs. time and the model of change rate of deformation vs. deformation rate under the coupling action of cooling and dynamic load were proposed and verified, which are helpful for the evaluation of engineering stability on saline soil subgrade fillings.